The Influence of the Science, Environment, Technology, and Society (SETS) Learning Model on Science Learning Outcomes for Grade VII Students on the Topic of Nature of Science and Scientific Methods - Hikmah, Nur; Zulhijah, Cita; Ismaun, Ismaun; Halmuniati, Halmuniati (KULIDAWA, 2024)
This research aims to: 1) interpret the influence of the Science, Environment, Technology, and Society (SETS) learning model on the science learning outcomes of grade VII students on the learning topic of the nature of science and scientific methods; 2) interpret the implementation of each stage of the SETS learning model. The present study is quantitative research carried out at SMP Negeri 15 Kendari from August to September 2023. The research sample included grade VII1 students as the control class and grade VII2 as the experimental class. The data collection technique for this research is tests that are analyzed descriptively and inferentially, as well as observations, to interpret the implementation of the SETS learning model. The results show that: 1) hypothesis test results show that the value of tcalculated is 98.96 > ttable 1.67 , so it can be concluded that the SETS learning model influences students' science learning outcomes in the nature of science and scientific method material; 2) the teacher and student experienced difficulties when the SETS learning model was applied to the topic of nature of science and scientific methods at the stages of invitation, concept introduction, application and evaluation, yet, they did not experience difficulties at the exploration stage.